(untitled) (Periphērica, 2020)
In this article, I draw on Sara Ahmed’s theorization of “queer phenomenology” to examine the re-orientation of memory discourses in Patricio Guzman’s Nostalgia de la luz (2010). In Nostalgia, the camera produces a metaleptic effect by meticulously framing, in a similar manner to that of a telescope, the background of the official historical narrative: the memory of the natural world. Guzmán’s metaleptic camera teaches us an interconnected “memory of the cosmos.” Yet this re-orientation of memory discourses is articulated from a family home that serves as a gendered orienting device. Following queer phenomenology, I trace the ways in which the documentary’s innovative treatment of memory is hindered by the heteropatriarchal orientation of the family home. I argue that, in Nostalgia, the memory of the heterosexual male subject is the one that is transmitted vertically within the heteropatriarchal family. In doing so, the documentary reproduces the familial and linear tropes that have dominated discourses of intergenerational memory transmission. Queer phenomenology warns us that Guzman’s call to “vivir en el frágil tiempo presente” is not merely a question of having or lacking memory. Memory is a matter of following, and returning, specific lines of orientation, at the expense of others.